Curcumin-based pyrazoline analogues as selective inhibitors of human monoamine oxidase A. Issue 7 (18th June 2018) - Nath, Chandrani; Badavath, Vishnu Nayak; Thakur, Abhishek; Ucar, Gulberk; Acevedo, Orlando; Mohd Siddique, Mohd Usman; Jayaprakash, Venkatesan
Abstract : Chlorine substitution on a 3, 5-diphenyl-pyrazoline derivative enabled potent and selective inhibition of hMAO-A; calculations suggest an "aromatic sandwich" orientation is responsible. Abstract : A series of 2-methoxy-4-(5-phenyl-4, 5-dihydro-1 H -pyrazol-3-yl)phenol (pyrazoline) derivatives (2–6 ) have been synthesized and tested for human monoamine oxidase (hMAO) inhibitory activity. The most active derivative (2 ) behaved as a competitive hMAO-A inhibitor, with an inhibition constant value of 0.08 μM and a strong hMAO-A selectivity ( K i (hMAO-B)/ K i (hMAO-A) > 1751). In addition, 2 exhibited little to no cytotoxic effects up to a 25 μM concentration and provided the best blood–brain barrier permeability among the derivatives synthesized. Molecular dynamics simulations revealed that a chlorine substituent at the para -position of the phenyl ring in2 enabled a π–π stacking interaction with Tyr407 and Tyr444 that resulted in the formation of an "aromatic sandwich" structure. Consequently, this tight-binding aromatic cage culminated in a dramatically reduced active site volume that is believed to be the origin of the observed selectivity between the hMAO-A and hMAO-B isozymes. Removal of the chlorine from2 disrupted the favorable intermolecular interactions and resulted in a selectivity change towards hMAO-B.